Generalised interval-valued intuitionistic fuzzy entropy with some similarity measures. (21st November 2019) - Tiwari, Pratiksha; Gupta, Priti
Interval-valued intuitionistic fuzzy environment is appropriate for the most of the practical scenarios involving uncertainty, vagueness and insufficient information such as pattern recognition, medical diagnoses and decision making, etc. Entropy, similarity, distance, inclusion and cross entropy measures are few methods used for the measuring uncertainty and classifying interval-valued intuitionistic fuzzy sets. This paper presents the generalised entropy measure for the interval-valued intuitionistic fuzzy sets and relation is established that is used to define the generalised similarity measures using the proposed entropy measure. Further, the proposed entropy measure is compared with some existing measure of entropy with the help of an illustrative example and lastly we have demonstrated how the proposed measure can be used in decision making.